1988
DOI: 10.1159/000118477
|View full text |Cite
|
Sign up to set email alerts
|

Viqualine in Resistant Depression: A Double-Blind, Placebo-Controlled Trial

Abstract: Viqualine dihydrochloride is a new molecule, which possesses strong serotonin reuptake inhibition properties and, at the same time, diazepam-like actions, such as [3H]-diazepam-binding inhibition and antipunishment effect. The drug was administered double-blindly to 10 patients suffering from major depression resistant to previous treatments with tricyclics. The comparison group (10 patients) received placebo. Lorazepam (10 mg/day) was also given to both groups. Viqualine proved to be significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Group 1, oestrogen 5-25 mg/day or, Group 2, placebo (of similar appearance). Previous medications were withdrawn 12 weeks 11/25 0/22 44% (25 to 63%) Improvement defined as 10 or more points reduction on HRSD Faravelli et al , 1988 20 ‘double-blind placebo-controlled trial assigned on a random basis’ In-patients with a diagnosis of major depressive episode (DSM-III-R). Score of at least 18 on HRSD, age between 18 and 65 years Previous episodes of major depression in which the patients showed poor response to treatment with tricyclic antidepressants at doses of at least 150 mg 5-day drug-free period.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Group 1, oestrogen 5-25 mg/day or, Group 2, placebo (of similar appearance). Previous medications were withdrawn 12 weeks 11/25 0/22 44% (25 to 63%) Improvement defined as 10 or more points reduction on HRSD Faravelli et al , 1988 20 ‘double-blind placebo-controlled trial assigned on a random basis’ In-patients with a diagnosis of major depressive episode (DSM-III-R). Score of at least 18 on HRSD, age between 18 and 65 years Previous episodes of major depression in which the patients showed poor response to treatment with tricyclic antidepressants at doses of at least 150 mg 5-day drug-free period.…”
Section: Resultsmentioning
confidence: 99%
“…There were four trials which compared a pharmacological agent with a placebo (Table 1). The agents investigated were oestrogen (Klaiber et al , 1979), viqualine (Faravelli et al , 1988), ketoconazole (Malison et al , 1999) and paroxetine (Tyrer et al , 1987). Two of these studies were also crossover trials from which we extracted data for the 2 weeks prior to crossover.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluvoxamine, another SSRI, had a 28% response rate in an inpatient study of patients with a history of TCA nonresponse (Delgado et al, 1988). Finally, Faravelli et al (1988) reported that an investigational SSRI, viqualine, was superior to placebo (five of ten versus zero of ten) in a small study of outpatients who had failed to respond to a TCA. Finally, Faravelli et al (1988) reported that an investigational SSRI, viqualine, was superior to placebo (five of ten versus zero of ten) in a small study of outpatients who had failed to respond to a TCA.…”
Section: Switching From a Tca To An Ssrimentioning
confidence: 99%
“…However, Nolen et al (1988b) found only 2 of 56 patients (4%) responded to fluvoxamine in a 4-week trial of 59 inpatients with TRD. Finally, Faravelli et al (1988) reported that an investigational SSRI, viqualine, was superior to placebo (five of ten versus zero of ten) in a small study of outpatients who had failed to respond to a TCA. In summary, most trials are consistent with the notion that SSRIs in TCA nonresponders are associated with a 30-SO% response rate.…”
Section: Switching From a Tca To An Ssrimentioning
confidence: 99%